2016
DOI: 10.1037/stl0000052
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extra-credit incentives on student submission of end-of-course evaluations.

Abstract: Online evaluations of courses, although reputedly useful to students, instructors, and administrators, have been very limited in most college courses because of low response rates. With this scarcity in mind, we evaluated the effects of 3 interventions involving contingent extra credit on improvement of course-evaluation response rates to online evaluations (N = 162). The 3 interventions consisted of a small individual extra-credit incentive, a small group extra-credit incentive, and a formative-evaluation str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…When decision makers use SET data to make high-stakes decisions (faculty hires, annual evaluations, tenure, promotion, teaching awards), institutions would be wise to take steps to ensure that SETs have acceptable response rates. Berk (2013) and others (Dommeyer et al, 2004; Jaquett, VanMaaren, & Williams, 2016; Nulty, 2008) discuss effective strategies to improve response rates for SETs. These strategies include offering empirically validated incentives, creating high-quality technical systems with good human factors characteristics, and promoting an institutional culture that clearly supports the use of SET data and other information to improve the quality of teaching and learning.…”
Section: Implications For Practicementioning
confidence: 99%
“…When decision makers use SET data to make high-stakes decisions (faculty hires, annual evaluations, tenure, promotion, teaching awards), institutions would be wise to take steps to ensure that SETs have acceptable response rates. Berk (2013) and others (Dommeyer et al, 2004; Jaquett, VanMaaren, & Williams, 2016; Nulty, 2008) discuss effective strategies to improve response rates for SETs. These strategies include offering empirically validated incentives, creating high-quality technical systems with good human factors characteristics, and promoting an institutional culture that clearly supports the use of SET data and other information to improve the quality of teaching and learning.…”
Section: Implications For Practicementioning
confidence: 99%
“…To illustrate, one investigation of varied inducement methods showed that taking no action to encourage completion of online evaluations led to a response rate of 29%, demonstration of the Website in class led to a rate of 53%, and a small grade incentive of one quarter of 1% of the total course grade led to a response rate of 87% (Dommeyer et al, 2004). Subsequent research has documented that extra-credit inducements can reliably produce nearly 100% participation (Jaquett et al, 2016). Overall, response rates actually vary more between teachers than they do between administration methods, and teachers can gather responses from the vast majority of students using rather modest interventions (Crews & Curtis, 2011; Stowell et al, 2012).…”
Section: Obtaining Datamentioning
confidence: 99%
“…If online evaluations must be completed outside of class, there are many strategies that teachers can use to increasing response rates; for example, teachers can emphasize the importance of the survey, demonstrate how to fill out the survey, provide repeated reminders, and offer incentives in the form of rewards or grades (Berk, 2012). Research clearly shows that these types of interventions can significantly increase response rates (Dommeyer, Baum, Hanna, & Chapman, 2004; Jaquett, VanMaaren, & Williams, 2016; Nulty, 2008). To illustrate, one investigation of varied inducement methods showed that taking no action to encourage completion of online evaluations led to a response rate of 29%, demonstration of the Website in class led to a rate of 53%, and a small grade incentive of one quarter of 1% of the total course grade led to a response rate of 87% (Dommeyer et al, 2004).…”
Section: Obtaining Datamentioning
confidence: 99%
“…Although extra credit offered to students as an incentive for participation in SoTL or DBER research would (ideally) be disclosed in the methodology, extra credit can also be offered for a variety of other reasons. The tasks for earning extra credit are not always tied to content mastery, including attending on‐campus events (Foltz et al 2021) and completing end‐of‐course evaluations (Jaquett, VanMaaren, and Williams 2016). This approach to extra credit could artificially inflate grades.…”
mentioning
confidence: 99%